T-type calcium channel Cav3.2 deficient mice show elevated anxiety, impaired memory and reduced sensitivity to psychostimulants - Gangarossa, Giuseppe; Laffray, Sophie; Bourinet, Emmanuel; Valjent, Emmanuel (Frontiers in Behavioral Neuroscience, 2014)
The fine-tuning of neuronal excitability relies on a tight control of Ca2+ homeostasis. The low voltage-activated T-type calcium channels (Cav3.1, Cav3.2 and Cav3.3 isoforms) play a critical role in regulating these processes. Despite their wide expression throughout the central nervous system, the implication of T-type Cav3.2 isoform in brain functions is still poorly characterized. Here we investigate the effect of genetic ablation of this isoform in affective disorders, including anxiety, cognitive functions as well as sensitivity to drugs of abuse. Using a wide range of behavioral assays we show that genetic ablation of the cacna1h gene results in an anxiety-like phenotype, whereas novelty-induced locomotor activity is unaffected. Deletion of the T-type channel Cav3.2 also triggers impairment of hippocampus-dependent recognition memories. Acute and sensitized hyperlocomotion induced by d-amphetamine and cocaine are dramatically reduced in T-type Cav3.2 deficient mice. In addition, the administration of the T-type blocker TTA-A2 prevented the expression of locomotor sensitization observed in wildtype mice. In conclusion, our data reveal that physiological activity of this specific Ca2+ channel is required for affective and cognitive behaviors. Moreover, our work highlights the interest of T-type channel blockers as therapeutic strategies to reverse drug-associated alterations.